Kylskåp i beredskap: Matförråd för vardag och kris - Marshall, Matilda (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2018)
What can we learn about everyday sustainability through the refrigerator and kitchen cupboards? This explorative article explores challenges and possibilities evolving from the materiality of food storage. Using ethnographic fieldwork from Swedish households and archive material, practices relating to food storage are discussed in the perspective of societal change and issues of sustainability. Food storage, I argue, is dynamic and reveals through its development and contents norms and perceptions about food consumption and everyday life. Modern domestic food storage, such as refrigerators and freezers, have facilitated a relocation of time between different domestic practices and enabled new and safer ways to store food. However, they are also perceived to complicate aspects of sustainable living, e.g. stocking up on food and vegetable gardening.